1985
DOI: 10.1021/bi00327a014
|View full text |Cite
|
Sign up to set email alerts
|

Mode of interaction of .beta.-hydroxy-.beta.-methylglutaryl coenzyme A reductase with strong binding inhibitors: compactin and related compounds

Abstract: The sodium salts of compactin (1) and trans-6-[2-(2,4- dichloro-6-hydroxyphenyl)ethyl]-3,4,5,6-tetrahydro-4-hydroxy-2H-pyran- 2-one (3) are inhibitors of yeast beta-hydroxy-beta-methylglutaryl coenzyme A (HMG-CoA) reductase. The dissociation constants are 0.24 X 10(-9) and 0.28 X 10(-9) M, respectively. Similar values have been reported for HMG-CoA reductase from mammalian sources [Endo, A., Kuroda, M., & Tanzawa, K. (1976) FEBS Lett. 72, 323; Alberts, A. W., et al. (1980) Proc. Natl. Acad. Sci. U.S.A. 77, 395… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(42 citation statements)
references
References 30 publications
3
39
0
Order By: Relevance
“…It was earlier reported that the inhibition of HMGR by mevastatin is competitive with respect to HMG-CoA in case of rat liver enzyme (Endo et al 1976). Mevastatin-mediated inhibition of yeast HMGR is reported to be competitive with respect to HMG-CoA (Nakamura and Abeles 1985). However, when the effect of mevastatin was tested on the native parasite HMGR enzyme, it caused 70 % inhibition at 20 μM of mevastatin concentration.…”
Section: Discussionmentioning
confidence: 97%
“…It was earlier reported that the inhibition of HMGR by mevastatin is competitive with respect to HMG-CoA in case of rat liver enzyme (Endo et al 1976). Mevastatin-mediated inhibition of yeast HMGR is reported to be competitive with respect to HMG-CoA (Nakamura and Abeles 1985). However, when the effect of mevastatin was tested on the native parasite HMGR enzyme, it caused 70 % inhibition at 20 μM of mevastatin concentration.…”
Section: Discussionmentioning
confidence: 97%
“…As shown experimentally, the K, values of these sulfones are much smaller than the K , of the substrate, but their affinity is not as high as that of the sulfoxides. vrobablv because the sulfur-oxvgen bond methylglutaryl-CoA reductase and the fungal metabolite compactin [18], the high affinity of this strong competitive inhibitor has been shown to arise from the presence, in one molecule, of a substrate part and a hydrophobic region permitting the binding to the active site as well as the anchoring to a hydrophobic pocket of the enzyme. The sulfoxides VIII and X have an affinity towards 3-hydroxy-3-methylglutaryl-CoA similar to that of compactin but are purely hydrophilic.…”
Section: Discussionmentioning
confidence: 99%
“…In a third set of experiments to support ClFDP binding to the C site, a series of pairwise preincubation-dilution assays was undertaken. These experiments were modeled after those described by Nakamura and Abeles to determine the site specificity of slow-onset and slow-release reversible inhibitors such as compactin for HMGCoA reductase, when high substrate concentrations render traditional substrate protection assays ineffective due to substrate inhibition (29). For hRNR the SA of α at 0.5 mM CDP, 15 mM Mg 2þ , and 3 mM ATP is reduced by half when [CDP] is increased to 10 mM, and increasing [Mg 2þ ] does not prevent the observed substrate inhibition.…”
Section: Which Imposes No Restrictions About [I] Relative To [E] (mentioning
confidence: 99%